(untitled) (International Journal of Engineering and Computer Science, 2017)
Biometrics is automated methods of identity verification or identification based on the principle of measurable physiological or behavioral characteristics. Their characteristics are unique and not duplicable or transferable. This paper mainly focuses on a multimodal that comprises of retinal scan, facial recognition and fingerprint scan. Being a very convenient and user friendly way of authentication it is preferred much these days but at the same time it must be secure and reliable enough to meet various security attacks. A biometric system is a system which recognizes the human characteristics and trails, which is use for identifications and access control.The recognition is done on the bases of physiology and behavior characteristics. A unimodal biometric system is one which has only the limited accuracy. So as to improve the accuracy and security of biometric systems researchers came up with the idea of the multi modal biometric system. A multi modal biometric system integrates the results of two or more biometric trails. This paper deals with the multimodal biometric system.